PENGARUH AROMATERAPI LAVENDER DAN PROGRESIVE MUSCLE RELAXTION (PMR) TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI DI WILAYAH SEPATAN - Khairunisa Putri Damayanti; Rina Puspita Sari; H.A.Y.G. Wibisono (Nusantara Hasana Journal, 2022)
Hypertension is often referred to as the dark killer, because it is a deadly disease without any symptoms. WHO estimates that currently the prevalence of hypertension is 22% globally of the total world population. Treatments that can be done for clients with hypertension include non-pharmacological therapy, namely giving Lavender Aromatherapy in combination with Progressive Muscle Relaxation. The purpose of this study was to determine the effect of lavender aromatherapy and progressive muscle relaxation (PMR) on reducing blood pressure in hypertensive patients in the Sepatan Region. The research method in this study used a quasi-experimental design with a pre-experiment one-group pre-post test design. The population was hypertensive patients in RT 004 / RW 006, Pisangan Jaya Village, Sepatan District, Tangerang Regency with 30 respondents. The sampling technique in this study was using purposive sampling. The analysis technique above uses Univariate and Bivariate analysis using Paired T Test. The results showed that there was an effect of lavender aromatherapy and progressive muscle relaxation (pmr) on reducing blood pressure in patients with hypertension, with the result, p value of 0.000 <0.05, it can be concluded that there is an effect of lavender aromatherapy and progressive muscle relaxation (pmr) on lowering blood pressure. blood pressure in patients with hypertension in RT 004 / RW 006, Pisangan Jaya Village, Sepatan District, Tangerang Regency. Conclusion: Combination of Lavender Aromatherapy and Progressive Muscle Relaxation is a non-pharmacological therapy that has been proven to be effective in reducing blood pressure in hypertensive patients.